(untitled) (Journal of Universal Science Research, 2023)
This article focuses on the metaphor of the medium of fiction and the coverage of its use in literature. We know that the most important weapon in fiction is the word. How effective and understandable it is to be delivered through the means of artistic representation. Metaphor is widely used not only in the Nazi way of fiction, but also in prose. Through this article, I would like to prove this term through examples, citing the use of it in fiction and the goals of the writer or poet in their works.